Proyecto de factibilidad para la creación de una microempresa productora y comercializadora de dulce de toronche, en el cantón Celica, de la provincia de Loja para el año 2016 - Silva Cabrera, Astrid Carolina (2017)
The purpose of this research is to carry out a "FEASIBILITY PROJECT FOR THE CREATION OF A MICROENTERPRISE PRODUCER AND COMMERCIALIZER OF DULCE DE TORONCHE, IN CANTÓN CELICA OF THE PROVINCE OF LOJA FOR THE YEAR 2016", considering the business opportunity that can To provide the use of innovative agricultural products such as toronche candy, based on the analysis of all factors involved and the contribution to the creation of economic enterprises. In order to achieve the objective of the research work "To carry out the feasibility study for the implementation of a micro-enterprise producing toronche candy in the canton Célica province of Loja", materials and methods were used to compile, analyze, synthesize and determine the Results obtained through the use of techniques such as the survey and interview and methods such as deductive and inductive respectively; Which helped to complement the research work. Five studies were developed which together facilitated the determination of the feasibility of investing in the project, through market research, technical study, legal and administrative study, financial study and evaluation, and environmental and social studies. The market study showed an effective demand of 108,007 bottles of 250gr of toronche sweet, in addition the study of the supply resulted in 50,196 bottles of 250gr of toronche sweet the balance of the analysis as Unsatisfied Demand of 57,811 bottles of 250gr for The year of study. The technical study shows us the Installed Capacity of 57,600 and a utilized capacity of 90% for year 1, 90% for year 2, 95% for year 3, 95% for year 4 and year 5 100% As used capacity of production of bottles of 250 gr of toronche sweet. The administrative legal study determined the "La Celestial" Fruit Industry will be of Limited Liability, which will be governed by the regulations for the purpose and the Superintendence of Companies. The results of the economic feasibility: NPV 38,238.09; PRC 3 years 10 months and 24 days; TIT 47,44.65%; RBC $ 1.40; AS-INCOME 0.92 and AS-COSTS 0.92.